Buckling response of functionally graded multilayer graphene platelet-reinforced composite plates with circular/elliptical cutouts supporting on an elastic foundation under normal and shear loads - Kalhori, Amin; Bayat, Mohammad Javad; Asemi, Kamran (Frontiers in Mechanical Engineering, 2023)
Present article deals with the buckling response of functionally graded multilayer graphene platelet ١٢ reinforced composite (FG-GPL RC) rectangular plates with circular/elliptical cutout resting on ١٣ Winkler-type elastic foundation under uniaxial and biaxial normal and shear loads. Rule of mixtures ١٤ and Halpin-Tsai approach are applied to obtain the effective Poisson's ratio, mass density and elastic ١٥ modulus of the reinforced composite, respectively. The governing equations are developed applying ١٦ the third-order shear deformation plate theory. Then, finite element procedure is used to solve the ١٧ problem. Four different types of GPL distribution that is UD, FG-X, FG-V and FG-O are considered. ١٨ A broad range of factors such as plate aspect ratio, plate slenderness ratio, applying uniaxial and ١٩ biaxial normal and shear loads to the plate, several Winkler elastic foundation stiffness parameters, ٢٠ different displacement boundary conditions, effect of size of circular and orientation of elliptical ٢١ cutout and finally influence of GPLs weight fraction are discussed in several tabular and graphical ٢٢ data in detail.